Experimental Investigation on the Properties of Borneo Soft Soil Stabilized with Industrial Waste - Prasetia, Irfan; Hutagamissufardal, Hutagamissufardal; Jimmy, Ahmad; Ananda, Muhammad Dhiya Khairi (International Journal of Engineering and Management Sciences, 2024)
This research aims to investigate the physical and mechanical properties of soft soil stabilized using industrial wastes, namely fly ash and rice husk ash. For this purpose, 6 (six) variations in the composition of fly ash (F), lime (L), and rice husk ash (R) were prepared. The variations in sample composition are SFLR1 (F: 15%, L: 2.5%, R: 5%), SFLR2 (F: 20%, L: 2.5%, R: 5%), SFLR3 (F: 25%, L: 2.5%, R: 5%), SFLR4 (F: 15%, L: 5%, R: 10%), SFLR5 (F: 20%, L: 5%, R: 10%) and SFLR6 (F: 25%, L: 5%, R: 10%). Meanwhile, soft soil was obtained from Banjarmasin City in South Borneo. The sample's physical properties were analyzed using the Atterberg limit test. Moreover, the California Bearing Ratio (CBR) and direct share tests are conducted to assess the sample's mechanical properties. The research results can provide confidence that fly ash, lime, and rice husk ash have the potential to improve the physical and mechanical properties of Borneo soft soil. The results of the Atterberg limit test show that industrial wastes can lower the liquid limit and increase the plastic limit; thus, the soil plasticity index decreases. As for the CBR test results, the untreated soft soil bearing ratio value of 1.4% can be increased to 2.6% after being treated with industrial wastes. In addition, using industrial wastes also decreases the swelling of the soil. Moreover, it can be seen that greater use of fly ash can improve the mechanical properties of the soft soil. However, increasing the composition of lime and rice husk ash can reduce the mechanical properties of the soft soil. Based on the experimental results, it is proposed to use SFLR3 as soil stabilization mixtures.